2014
DOI: 10.1371/journal.pone.0100624
|View full text |Cite
|
Sign up to set email alerts
|

Flapless versus Conventional Flapped Dental Implant Surgery: A Meta-Analysis

Abstract: The aim of this study was to test the null hypothesis of no difference in the implant failure rates, postoperative infection, and marginal bone loss for patients being rehabilitated by dental implants being inserted by a flapless surgical procedure versus the open flap technique, against the alternative hypothesis of a difference. An electronic search without time or language restrictions was undertaken in March 2014. Eligibility criteria included clinical human studies, either randomized or not. The search st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 30 publications
2
36
0
5
Order By: Relevance
“…First of all, all confounding factors may have affected the long-term outcomes and not just the fact that implants were placed in fresh extraction sockets patients or in healed sites, and the impact of these variables on the implant survival rate, postoperative infection and marginal bone loss [105][106][107][108][109][110][111] is difficult to estimate if these factors are not identified separately between the two different procedures in order to perform a meta-regression analysis. The lack of control of the confounding factors limited the potential to draw robust conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…First of all, all confounding factors may have affected the long-term outcomes and not just the fact that implants were placed in fresh extraction sockets patients or in healed sites, and the impact of these variables on the implant survival rate, postoperative infection and marginal bone loss [105][106][107][108][109][110][111] is difficult to estimate if these factors are not identified separately between the two different procedures in order to perform a meta-regression analysis. The lack of control of the confounding factors limited the potential to draw robust conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless this approach will be promising future for esthetic zone areas without any intervention for alveolar bone exposure or soft tissue reflection. Recent studies reported identified risk factors for flapless implant surgeries such as type 4 bone, smoking, periodontal disease, the immediate loading only in the flapless group in some studies is a confounding factor, the use of grafts, the use or not use of surgical guides, different prosthetic configurations, and the insertion of implants from different brands and surface treatments [23][24][25][26].…”
Section: Main Outcomes Of Selected Studiesmentioning
confidence: 99%
“…To ensure less trauma during surgical placements of dental implants, and less surgical time, a flapless technique can be used with the aid of a surgical stent but it requires a good bone quality 10 . It is regarded as a blind procedure and the operator cannot evaluate the alveolar bone quality 4 ; therefore, it needs an advanced clinical experience and surgical judgment 8,11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…The disadvantages of the flapless surgical technique include inability to visualize anatomical landmarks, thermal damage due to reduction of coolant irrigation during preparing the socket, and mal-posed angle of dental implants 8,11,12 . The advantages of the flapped surgical procedure are: it provides good access to the implant site, allows good visualization to anatomical landmarks, and allows bone graft placement, when required 8,11,12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation